Ihwal Penerapan Hukum Islam di Indonesia - Ines Romadona Aditya Putri; Ashif Az Zafi (IAIN Syekh Nurjati Cirebon, 2020)
The assembling of Islamic law in Indonesia has faced obstacles since it began to enter Western law into Indonesia. So that several legal theories were born in response to the friction between Western law and Islamic law. The recipe theory is one of the Dutch strategies to discredit and reduce Islamic law that has prevailed in Indonesia. Then, came the theory of Exept law Exit and Receptio a Contrario which is one form of resistance as proof that Islamic law still exists in Indonesia. There are two problems that greatly influence the application of Islamic law in Indonesia. This paper explains the problem of applying Islamic law in Indonesia. This discussion is focused on the entry of Western law into Indonesia and its contact with customary law that already applies to Indonesian society, and the second is the influence of political and cultural society. This paper is the result of literature research.